DESKRIPSI MANFAAT KURIKULUM MERDEKA TERHADAP PEMBELEJARAN MATEMATIKA SISWA KELAS VII DI SMP NEGERI 3 PAREPARE - Sofia Sofia; Asrinan; Abdul Rahman (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2025)
The purpose of this study is to describe the benefits of the Merdeka Curriculum in mathematics learning, specifically on the topic of Basic Statistics for Grade VII.7 students at SMP Negeri 3 Parepare. This research employ-ed a descriptive qualitative approach. Data analysis was carried out in three stages: data reduction, data presentation, and verification or conclusion drawing. The validity of the data was examined using time triangulation. The research subjects were 29 students of Grade VII.7, but data analysis was conducted on 26 students, as 3 students were absent during data collection. The research instruments included observation sheets, a four-point Likert scale questionnaire, and interview guides developed based on three indicators: student independence, active participation, and material relevance. Data were collected through classroom observations on Basic Statistics, questionnaire distribution, interviews with three students representing high, medium, and low ability categories, and documentation. The findings indicate that the implementation of the Merdeka Curriculum has a positive impact on mathematics learning in Basic Statistics. The curriculum fosters student independence, enhances active participation, and facilitates better understanding of the material, as it is presented contextually and aligned with students’ needs.